Friend or fiend? with the Pain & the Great One - Blume, Judy.; Stevenson, James, 1929- (New York : Delacorte Press, 2009)
A reading circle mishap convinces Jake that he never wants to speak during class again and Abigale loses her trust in one of her best friends, but they both have to deal with their fiendish cousins from New York.
Booklist.
Horn Book.
Booklist, April 2009.
Horn Book, October 2009.
2.8
K-3
Keywords: Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Schools -- Juvenile fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Schools -- Fiction; Family life -- Fiction; School stories; Siblings -- Fiction